Do shifts in self-descriptions occur when the concept of self-image is mediated to teenage learners through creative movement? - February, Alexa (School of Education, 2021)
This thesis sought to explore whether an intervention using Creative Movement could improves the ways in which teenagers described themselves. The theoretical framework of L.S. Vygotsky (1978) was employed as a lens through which to understand the concepts of self-image, mediation, identity and adolescence. An eight week programme was devised by the researcher in which eight volunteer participants at two local South African secondary schools used improvised Creative Movement in various activities facilitated by the researcher. These activities explored various aspects of the self in an attempt to mediate participants towards positive and stable self-description. Data were collected by way of a pre- and post-test in which participants were required to self-describe in a series of written and verbal responses to open and closed questions. The pre- and post-tests were compared in order to track any shifts in self description. These tests included a self-esteem inventory, open-ended written questions and a personal interview. Further data were collected during the intervention in the form of journals kept by participants and observation schedules. Qualitative and quantitative analysis was performed. Quantitative analysis included t-tests in order to ascertain statistical significance of any shifts observed. The research conducted found that significant positive shifts in self-description did occur in all eight participants. Further findings involved the relationship between these shifts and the Zone of Proximal Development and the social structures in which participants found themselves. It was also noted that Creative Movement served as an excellent mediational tool for the concept of self-image.